Less Severe Cases of COVID-19 in Sub-Saharan Africa: Could Co-infection or a Recent History of Plasmodium falciparum Infection Be Protective? - Kalungi, Allan; Kinyanda, Eugene; Akena, Dickens Howard; Kaleebu, Pontiano; Bisangwa, Innocent M. (Frontiers in Immunology, 2021)
Sub-Saharan Africa has generally experienced few cases and deaths of coronavirus disease 2019 (COVID-19). In addition to other potential explanations for the few cases and deaths of COVID-19 such as the population socio-demographics, early lockdown measures and the possibility of under reporting, we hypothesize in this mini review that individuals with a recent history of malaria infection may be protected against infection or severe form of COVID-19. Given that both the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and Plasmodium falciparum (P. falciparum) merozoites bind to the cluster of differentiation 147 (CD147) immunoglobulin, we hypothesize that the immunological memory against P. falciparum merozoites primes SARS-CoV-2 infected cells for early phagocytosis, hence protecting individuals with a recent P. falciparum infection against COVID-19 infection or severity. This mini review therefore discusses the potential biological link between P. falciparum infection and COVID-19 infection or severity and further highlights the importance of CD147 immunoglobulin as an entry point for both SARS-CoV-2 and P. falciparum into host cells.